Effects of trash box design on solid waste segregation behaviors - Marcial, Jobelle V.; Tibon, Noriza R.; Tanchuling, Maria Antonia N. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study was conceptualized because, despite the presence of segregation bins, the solid wastes collected by janitors are still unsorted. The study was designed to determine if the trash box design has something to do with the decision of the waste generator to segregate. It also aims to assess the condition of solid waste segregation in some of the buildings in UP and to propose improvements on the existing solid waste segregation schemes. This is done by selecting four buildings in UP with different trash bin design. The four selected buildings are Melchor Hall, Benitez Hall, Palma Hall Annex and Alonso Hall. Waste characterization and survey were conducted in the selected buildings. Findings in this study show that the segregation of wastes in these buildings is not that efficient with waste characterization results of 64.17% and survey results of 53.15%. The highest segregation efficiency is recorded from Benitez Hall. Majority of the students said that they are segregating but waste sorting survey results show that they can be confused in classifying the wastes. For the students who are not segregating at all and for those who segregate some of the time, reasons for not segregating can be classified into four major factors: time, trash bin design and appearance, environment and behavior towards segregation. Majority of the students said that their decision to segregate will be affected by the trash bin design, thus, providing properly designed trash bins that may aid in more efficient solid waste management in the university can be a good investment. Respondents preferred multi-colored trash bins with waste classification and pictures as label on the face of the bin. The proposed trash bins have four classifications consistent with the guidelines regarding the solid waste management in UP Diliman. An affirmative instruction was also posted to encourage the waste source to segregate. It is suggested that a specific color should be fixed for each type of waste so that color itself can be an identification. However, this design, no matter how colorful or detailed it is, will only be effective with proper implementation and monitoring and with the compliance of students and staff. The education of students and staff regarding the classification of wastes should also be taken into action. It is recommended for further studies to test the proposed trash bin design for different settings.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Refuse and refuse disposal; Recycling (Waste); Integrated solid waste management